2021
DOI: 10.1111/1365-2745.13674
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use history alters the diversity, community composition and interaction networks of ectomycorrhizal fungi in beech forests

Abstract: 1. Forests have expanded across Europe over the last centuries as a consequence of farmland (agricultural and pasture) abandonment. Agricultural practices usually increase soil fertility and reduce the diversity and abundance of ectomycorrhizal (ECM) fungi, essential mutualists of many woody species in temperate and Mediterranean forests. The recovery of this biotic interaction after the cessation of human activities is, thus, crucial for the re-establishment of functional forest ecosystems.2. Here we addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 185 publications
(185 reference statements)
1
15
0
Order By: Relevance
“…For fungi, n = 156 and n = 28 for continent and island ecoregions, respectively; for other groups, n = 76 and n = 14 for continent and island ecoregions, respectively. be more influential locally (e.g., Correia et al, 2021;van der Linde et al, 2018) and are partly accounted for by land cover change in this study. Furthermore, while here we calculated average vulnerabilities by summing the effects of individual drivers, global change impacts tend to be synergistic (Rillig et al, 2019), so actual vulnerabilities may be much higher.…”
Section: Vulnerability To Global Change Driversmentioning
confidence: 83%
“…For fungi, n = 156 and n = 28 for continent and island ecoregions, respectively; for other groups, n = 76 and n = 14 for continent and island ecoregions, respectively. be more influential locally (e.g., Correia et al, 2021;van der Linde et al, 2018) and are partly accounted for by land cover change in this study. Furthermore, while here we calculated average vulnerabilities by summing the effects of individual drivers, global change impacts tend to be synergistic (Rillig et al, 2019), so actual vulnerabilities may be much higher.…”
Section: Vulnerability To Global Change Driversmentioning
confidence: 83%
“…Both families tend to be hostgeneralists that are abundant in subtropical and tropical oak forests (García-Guzmán et al, 2017). Some species from these families also have short-exploration type hyphae that allow them to regenerate faster compared to taxa with greater extraradical hyphae, thus recovering more easily from disturbances (Deslippe et al, 2011;Correia et al, 2021). To date a limited number of ECM fungal species, mostly from temperate and boreal regions, have been tested for reforestation purposes (Policelli et al, 2020).…”
Section: Ectomycorrhizal Fungal Network As a Tool In Forest Restorationmentioning
confidence: 99%
“…The effect of disturbance may contribute to the presence of rare ECM taxa (Kałucka and Jagodziński, 2016). For example, Tarzetta is an early-successional ascomycete that abundantly colonizes seedlings across different forest ecosystems, particularly in sites that face environmental stress or disturbance (Correia et al, 2021). Similarly, species of Peziza are stress-tolerant taxa that can intensely colonize roots following fire disturbances (Pulido-Chavez et al, 2021), while the basidiomycete genus Entoloma is frequently found in fragmented young forest stands and is not very prone to dispersal limitation (Boeraeve, 2019).…”
Section: Mycorrhizal Associations Across Plant Hosts and Sitesmentioning
confidence: 99%
“…From a plant-centered perspective, the reported pauperization effect of forest exploitation on ECM communities may alter the topology of ECM networks. Early evidence of age influence on network topology already exists: using high-throughput sequencing of soils, Correia et al (2021) reported contrasted ECM network topologies along a chronosequence of Fagus sylvatica forest establishment, plant nodes in long-established forests presenting higher numbers of connection links than in recent patches. From a fungal perspective, silvicultural practices tend to reduce the number and diversity of available plant nodes for fungal genets.…”
Section: In Cultivated Ecosystems Anthropic Practices Affect Ectomyco...mentioning
confidence: 99%
“…As organisms are highly dependent on soil physico-chemical conditions, ECM fungal communities are critical components of soil history by responding to short-term as well as long-term human impacts (Dupouey et al, 2002). Inevitably, the composition and dynamics of ECM community are profoundly influenced by forest management (Tomao et al, 2020) and anthropic disturbance derived from agronomic practices in man-made ecosystems (Olivera et al, 2014;Taschen et al, 2015), with cascading effects on the underlying interaction networks (Correia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%